PENDAMPINGAN PETERNAK TENTANG PENGUATAN STRATEGI KETERSEDIAAN PAKAN SAPI PEDAGING MELALUI FOCUS GROUP DISCUSSION BERSAMA PEMANGKU KEPENTINGAN DI KABUPATEN MUNA - Nasiu, Firman; Nafiu, La Ode; Abadi, Musram; Gerhana, Gerhana; Auza, Fuji Astuty; Asminaya, Nur Santy; Agustina, Dian; Tasse, Andi Murlina; Yunus, Lukman; Zani, Munirwan; Gandri, La; Manginsi, Wa Ode Jumiarni; Kundarita, Kundarita; Setiawati, Indra Rahayu; Safitri, Safitri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2025)
Feed availability is a key factor in increasing beef cattle productivity. This activity aims to strengthen beef cattle feed availability strategies through a collaborative approach involving all relevant stakeholders in Muna Regency. This FGD activity was held in August 2025 in one of the beef cattle development centers in Kabangka District, Muna Regency. FGD participants consisted of various important elements, including the Southeast Sulawesi Regional Research and Innovation Agency (BRIDA) Team, the Halu Oleo University (UHO) Research Team, the Muna Regency Livestock and Animal Health Service (PKH) Team, the Kabangka Subdistrict Agricultural Extension Center (BPP), and local farmers. The data obtained from the FGD was analyzed using descriptive methods. The main strategies recommended are the application of feed processing technology, crop-livestock integration, increasing the capacity of livestock farmers, and protecting grazing land. Therefore, together with stakeholders in Muna Regency, it can become a driving force in developing the beef cattle industry in Muna Regency. The results obtained show that Muna Regency has great potential for beef cattle development, supported by its population and availability of land, natural resources, and feed from agricultural waste. However, this potential is constrained by low feed quality, traditional management systems, and limited knowledge and infrastructure among farmers. The main strategies recommended are the application of feed processing technology, crop-livestock integration, increasing the capacity of livestock farmers, and protecting grazing land. Therefore, together with stakeholders in Muna Regency, this can be a driving force in overseeing the development of beef cattle.